FATWA DSN NO. 15/DSN-MUI/IX/2000 TERHADAP IMPLEMINTASI PENGHITUNGAN NISBAH PADA PEMBIAYAAN MUDHARABAH DI KJKS BMT-UGT SIDOGIRI CAPEM LICIN BANYUWANGI - Firdaus, Muhammad (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2023)
Mudharabah financing has become one of the main instruments in Islamic banking used to support economic and financial development in accordance with Islamic principles. Therefore, it is important to understand and apply relevant sharia guidelines in the management of Mudharabah financing. DSN Fatwa No. 15/DSN-MUI/IX/2000 is one of the important guidelines issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) to regulate the implementation of ratio calculation in Mudharabah financing. This study aims to analyze how the Fatwa is implemented in the context of the Sharia Financial Services Cooperative (KJKS) Baitul Maal wat Tamwil (BMT) - Unit Guna Usaha Tani (UGT) Sidogiri Branch Four (Capem) Licin, Banyuwangi. The research method used is a case study by collecting data through interviews with the manager of KJKS BMT-UGT Sidogiri Capem Licin, observation, and analysis of related documents. The results showed that the implementation of DSN Fatwa No. 15/DSN-MUI/IX/2000 in calculating the ratio at KJKS BMT-UGT Sidogiri Capem Licin Banyuwangi has been running in accordance with the established sharia guidelines. This study also identifies the challenges faced by KJKS in implementing the Fatwa, including regulatory changes and operational constraints. However, KJKS' efforts in facing these challenges have ensured that Mudharabah financing remains in accordance with sharia principles. 1. the profit-sharing calculation system in mudharabah financing at KJKS BMT-UGT Sidogiri Capaem Licin uses the revenue sharing method. 2. the revenue sharing method used by KJKS BMT-UGT Sidogiri Capaem Licin is in accordance with DSN Fatwa No. 15/DSN-MUI/IX/2000.